Pengaruh Promo Tanggal Kembar, Gratis Ongkos Kirim, Metode Pembayaran S-Pay Later Terhadap Keputusan Pembelian Di Marketplace Shopee - Nosaly, Ferdy Satya; Andriana, Ana Noor (Journal of Business and Economics Research (JBE), 2024)
This study aims to examine the effect of the Twin Date Promo, Free Shipping, and S-Pay Later Payment Method on Purchasing Decisions at the Shopee marketplace. This research uses quantitative methods with a descriptive approach. The sample calculation uses the Lemeshow formula because the population is not known with certainty. The sample consisted of 100 Shopee user respondents in Samarinda City who were selected using purposive sampling technique. The data collection technique was carried out through an online questionnaire using Google Form and physical distribution of questionnaires directly to respondents who fit the criteria of research respondents who have made purchases at Shopee and live in the city of Samarinda. Data analysis using multiple linear regression and hypothesis testing with the help of SPSS. The results showed that the Twin Date Promo has a positive and significant effect on Purchasing Decisions with a t-count value (2.787) > t-table (1.984) with a significance level smaller than 0.05. Free Shipping has a positive and significant effect on Purchasing Decisions with a t-count value (4.669) > t-table (1.984) with a significance level smaller than 0.05, while the S-Pay Later Payment Method has no positive and significant effect on Purchasing Decisions t-count (1.502) < t-table (1.984) with a significance level greater than 0.05. Simultaneously, the three independent variables have a positive and significant effect on Purchasing Decisions assessed by F count (24.371) > F table (2.47), and the significance level is smaller than α = 0.05.